Upaya Peningkatan Ekonomi Keluarga melalui Pendampingan Anyaman Pandan oleh Mahasiswa KKN - Hasbi Assidik; Kristina Kristina; Danang Hariyanto; Muhammad Faris; Muji Muji (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The Community Service Program (KKN) is a form of implementing the Tri Dharma of Higher Education, particularly in community service. This program not only involves student participation but also explores the potential and needs of the local community. From July 16 to August 31, 2025, students from the Islamic Counseling and Arabic Language Education Study Program of Hidayatullah Islamic Institute Batam carried out a KKN program in Kampung Tua Tanjung Gundap, Sagulung District, Batam City. The main focus was to assist residents in developing a pandan leaf weaving business as one of their income sources. Activities included observation, product innovation socialization, weaving process assistance, and evaluation. The community showed improved skills in producing woven crafts such as mats, baskets, and table covers, which became more attractive and had higher market value. In addition, residents received basic training in marketing strategies, both offline and through digital platforms, to expand their market reach. This program has contributed to enhancing community economic independence while strengthening cooperation between students and local residents. Moreover, it serves as a learning experience for students to apply their academic knowledge in real-life community settings.